2020
DOI: 10.1590/1678-7757-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal anesthetic gel for pain control during periodontal therapy in adults: a placebo-controlled RCT

Abstract: Periodontal therapy usually requires local anesthesia. If effective, a non-invasive, liposomal anesthetic gel could increase the levels of acceptance of patients in relation to periodontal therapy.Objective:This study investigated the efficacy of liposomal anesthetic gel for pain control during periodontal therapy.Methodology:Forty volunteers with moderate to severe chronic periodontitis were recruited, of which at least three sextants required periodontal therapy. At least one of the selected teeth had one si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The most prevalent study design was the parallel design, which was used in 15 studies [ 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ], followed by the split-mouth design, which was used in 10 [ 30 31 32 33 34 35 36 37 38 39 ], and the crossover design, which was used in 7 studies [ 40 41 42 43 44 45 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most prevalent study design was the parallel design, which was used in 15 studies [ 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ], followed by the split-mouth design, which was used in 10 [ 30 31 32 33 34 35 36 37 38 39 ], and the crossover design, which was used in 7 studies [ 40 41 42 43 44 45 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes were used by Moraes et al to promote pain control during scaling and root planning treatment. The liposomes loaded with lidocaine/prilocaine could be a good option to increase patient compliance during this type of clinical treatment, especially anxious patients or those who have a fear of needles [ 45 ].…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…Periodontal therapy usually requires also local anesthesia. A liposomal lidocaine/prilocaine, thermosetting anesthetic gel formulation delivered into periodontal pocket was investigated for pain control during scaling and root planing (anti-infective periodontal therapy) in 40 volunteers with moderate to severe chronic periodontitis [70]. It was reported that the intra-pocket anesthetic gel would be a good option for anxious patients, or those who have a fear of needles.…”
Section: Liposomesmentioning
confidence: 99%